2003
DOI: 10.1086/378739
|View full text |Cite
|
Sign up to set email alerts
|

Response to Lamivudine Treatment in Children with Chronic Hepatitis B Virus Infection

Abstract: Despite the recent approval of lamivudine for the treatment of children with chronic hepatitis B virus (HBV) infection, there is insufficient information on the kinetics of HBV clearance and the factors that predict a favorable treatment response to lamivudine in this population. In a small retrospective study of 16 HBV-infected children treated with lamivudine, we examined changes in virus load and other factors associated with hepatitis B e antigen (HBeAg) clearance. High pretherapy alanine aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
2
16
3
Order By: Relevance
“…The above‐mentioned background information requires us to focus the treatment in patients acquiring HBV infection through maternal transmission. Our data suggest lamivudine did not achieve a better response rate in the treatment group as compared with the control group and some previous pediatric studies 10,19 . Spontaneous HBeAg seroconversion of maternally transmitted carriers commonly occurs between the ages of 15 and 30 years.…”
Section: Discussioncontrasting
confidence: 52%
“…The above‐mentioned background information requires us to focus the treatment in patients acquiring HBV infection through maternal transmission. Our data suggest lamivudine did not achieve a better response rate in the treatment group as compared with the control group and some previous pediatric studies 10,19 . Spontaneous HBeAg seroconversion of maternally transmitted carriers commonly occurs between the ages of 15 and 30 years.…”
Section: Discussioncontrasting
confidence: 52%
“…Mutations conferring resistance to lamivudine occur particularly in the highly conserved tyrosine‐methionine‐aspartic acid‐aspartic acid (YMDD) motif of the catalytic domain (C domain) of the polymerase. Smaller studies of LAM treatment in children have confirmed both the efficacy in reducing serum HBV‐DNA and the high mutation rate . Several authors have recommended continuing therapy for at least 6 months after HBeAg seroconversion or until virological breakthrough occurs, but the optimal treatment duration remains unknown.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Jonas et al [9] determined a relapse rate of 17.5% in a placebo controlled LAM trial in children. Hagmann et al [10] found relapse rate of 25% after cessation of LAM treatment. It is likely that duration of LAM treatment would be a culprit for the variations in relapse rates.…”
Section: Resistance In Childrenmentioning
confidence: 99%
“…Interestingly, YMDD mutation rate of this study was extremely higher than other studies. Hagmann et al [10] reported development of clinical resistance to LAM in 3 children (19%) in the first year of therapy. Furthermore, in this study, frequency of drug resistance is found to be low in children with high HBV-DNA suppression level.…”
Section: Resistance In Childrenmentioning
confidence: 99%
See 1 more Smart Citation